FACTOR VIII MAY PREDICT CATHETER-RELATED THROMBOSIS IN CRITICALLY ILL CHILDREN: A PRELIMINARY STUDY - Faustino, Edward Vincent S. (Pediatr Crit Care Med, 2015)
OBJECTIVE: If we can identify critically ill children at high risk for central venous catheter-related thrombosis, then we could target them for pharmacologic thromboprophylaxis. We determined whether factor VIII activity or G value was associated with catheter-related thrombosis in critically ill children. DESIGN: Prospective cohort study SETTING: Two tertiary academic centers PATIENTS: We enrolled children <18 years old who were admitted to the pediatric intensive care unit within 24 hours after insertion of a central venous catheter. We excluded children with a recently diagnosed thrombotic event or those anticipated to receive anticoagulation. Children with thrombosis diagnosed with surveillance ultrasonography on the day of enrollment were classified as having prevalent thrombosis. Those who developed catheter-related thrombosis thereafter were classified as having incident thrombosis. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: We enrolled 85 children in the study. Once enrolled, we measured factor VIII activity with one-stage clotting assay and determined G value with thromboelastography. Of those enrolled, 25 had incident and 12 had prevalent thromboses. The odds ratio for incident thrombosis per standard deviation increase in factor VIII activity was 1.98 (95% confidence interval: 1.10-3.55). The area under the receiver operating characteristic curve was 0.66 (95% confidence interval: 0.52-0.79). At factor VIII activity >100 IU/dL, which was the optimal threshold identified using Youden index, sensitivity and specificity were 92.0% and 41.3%, respectively. The association between factor VIII activity and incident thrombosis remained significant after adjusting for important clinical predictors of thrombosis (odds ratio: 1.93; 95% confidence interval: 1.10-3.39). G value was associated with prevalent but not with incident thrombosis. CONCLUSION: Factor VIII activity may be used to stratify critically ill children based on their risk for catheter-related thrombosis.